2020
DOI: 10.1016/j.jenvrad.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide transfer to wildlife at a ‘Reference site’ in the Chernobyl Exclusion Zone and resultant radiation exposures

Abstract: This study addresses a significant data deficiency in the developing environmental protection framework of the International Commission on Radiological Protection, namely a lack of radionuclide transfer data for some of the Reference Animals and Plants (RAPs). It is also the first study that has sampled such a wide range of species (invertebrates, plants, amphibians and small mammals) from a single terrestrial site in the Chernobyl Exclusion Zone (CEZ). Samples were collected in 2014 from the 0.4 km sampling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 33 publications
7
66
0
Order By: Relevance
“…2500 t of Pb were dropped onto the burning reactor (National Report of Ukraine, 2011)). However, a study conducted on a terrestrial site in the Red Forest, found levels of Pb in soil typical for European soils (Beresford et al, 2019b), which agrees with Jagoe et al, (1998) who found no elevated Pb (or Hg) concentrations in freshwater ecosystems close to the Chernobyl NPP. Hence, based on current evidence, it seems unlikely that there is widespread non-radiological contamination in the CEZ because of the accident.…”
Section: The Cez As a Multi-stressor Environment?supporting
confidence: 73%
“…2500 t of Pb were dropped onto the burning reactor (National Report of Ukraine, 2011)). However, a study conducted on a terrestrial site in the Red Forest, found levels of Pb in soil typical for European soils (Beresford et al, 2019b), which agrees with Jagoe et al, (1998) who found no elevated Pb (or Hg) concentrations in freshwater ecosystems close to the Chernobyl NPP. Hence, based on current evidence, it seems unlikely that there is widespread non-radiological contamination in the CEZ because of the accident.…”
Section: The Cez As a Multi-stressor Environment?supporting
confidence: 73%
“…There could be a localised dose from 90 Sr to the gut surface, but within one order of magnitude of the estimated internal dose rate, although localised dose may be similar. The dominance of external exposure due to 137 Cs and the relative contributions of the different radionuclides to internal dose are in agreement with dose estimates based upon radionuclide activity concentrations measured in earthworms (Lumbricidae) and soil sampled from the Red Forest (CEZ) in 2014 (Beresford et al, 2019a).…”
Section: Soil Analysis and Dosimetry Modelingsupporting
confidence: 79%
“…Radiation data were right skewed, so the radiation measurements were log 10 -transformed to achieve normality. A recent study shows that approximately 70% of radiation dose of Chernobyl bank voles comes from external sources of Cs 137 and Sr 90 (Beresford et al 2020). However, IR also accumulates in plant tissue, which is eaten by animals and increase their exposure (Boraty nski et al 2016).…”
Section: Study Animalsmentioning
confidence: 99%
“…Long-lived radioactive compounds, such as cesium-137 (Cs 137 ) and strontium-90 (Sr 90 ) from Fukushima and Chernobyl, have spread far in landscape scale and due to their long half-life (approximately 30 years) the effects persist for decades (Askbrant et al 1996;IAEA 1996;Baba 2013). In Chernobyl area, many species gain most of their radiation burden externally and accumulation of Cs 137 and Sr 90 is species-specific (Beresford et al 2020). Due to its water solubility, Cs 137 has high mobility and enters the body through the diet and drinking water (Murakami et al 2015).…”
Section: Introductionmentioning
confidence: 99%